Using a layer based on materials with a metal to semiconductor phase transition for electrothermal protection of solar cells - Alexander Tonkoshkur; Alexander Ivanchenko (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
One of the main problems in ensuring the reliability of solar electrical power sources is local overheating, when hot spots form in photovoltaic cells of solar arrays. It is currently considered that these negative phenomena are caused, among other things, by overvoltage in the electrical circuits of solar arrays. This leads to the appearance of defective elements and a significant decrease in the functionality of the entire power generation system up to its complete failure. This study considers the possible ways to increase the reliability of solar arrays by using thermistor thermocontacting layers for preventing overvoltage events and overheating. The authors use simulation to study electrical characteristics of a photovoltaic cell in thermal contact with an additional layer based on thermistor materials with a metal to semiconductor phase transition. Vanadium dioxide with a phase transition temperature of ~340 K is considered to be a promising material for this purpose. During the phase transition, electrical resistance sharply decreases from the values characteristic of dielectrics to the values associated with metal conductors. It is shown that such thermistor layers can be used for protecting solar cells from electrical overheating under the following basic conditions: — the layer’s resistance in the «cold» state significantly exceeds that of the lightened forward-biased solar cell; — the layer’s resistance in the «heated» state is sufficiently low compared to those of the reverse-biased photovoltaic cell and of the power source. The current and temperature of the reverse-biased photovoltaic cell are limited and stabilized, and the voltage drop sharply decreases from the moment when the temperature of the thermistor layer reaches the values close to the temperature of its transition to the low-conductivity state. The obtained results substantiate the potntial of the described approach to protect photovoltaic cells of solar modules against electric thermal overloads.